Intermediate structure of separation between grades in The Italica Amphitheater (Santiponce, Spain) - Mendoza Álvarez, José David (2018)
We intend to show the restitution of the Itálica amphitheater (Santiponce, Spain), which presents the disappeared superior levels. Thanks to the reinterpretation of images, texts, archives, documents and photographs from different periods, we have managed to restore its correct form in terms of the number of steps of each level, facades, perimeter staircase, architecture, historiography, geometry and capacity, objectives of this investigation